Attitude Of Women In The Novel Of Heaven Bidadaries Tere Liye's Work A Critical Review Of Feminism Literature - Ismizakiy; Fitriani, Yessi; Yunda, Arif (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to describe the attitudes of female characters contained in Tere Liye's novel Bidadari-Bidadari Surga by Tere Liye and to determine the form of literary criticism of feminism as a review of literary criticism in Tere Liye's novel Bidadari-Bidadari Surga by Tere Liye. This research is a qualitative research. Based on the results of research and discussion of the novel Bidadari-Bidadari Surga by Tere Liye as follows: The attitude of the female main character in Tere Liye's novel Bidadari-Bidadari Surga by Tere Liye covers three aspects including aspects of love, education and economics. The main character in the novel Bidadari-Bidadari Surga is Laisa. She is a woman who is tough and never gives up. Laisa's feelings of love and affection for her four younger siblings, namely Dalimunte, Wibisana, Ikanuri and Yashinta make Laisa willing to sacrifice anything for the sake of her sister's happiness. In terms of education, Laisa wants her younger siblings to get a higher education and a better future. Until finally, with such great attitude and sacrifice, Laisa was able to educate her younger siblings up to college. Meanwhile, in terms of economy, Laisa is able to change the life of her family and also her village for the better.